Electrical stimulation of titanium to promote stem cell orientation, elongation and osteogenesis. (February 2022) - Khaw, Juan Shong; Xue, Ruikang; Cassidy, Nigel J.; Cartmell, Sarah H.
Abstract: Electrical stimulation of cells allows exogenous electric signals as stimuli to manipulate cell growth, preferential orientation and bone remodelling. In this study, commercially pure titanium discs were utilised in combination with a custom-built bioreactor to investigate the cellular responses of human mesenchymal stem cells via in-vitro functional assays. Finite element analysis revealed the homogeneous delivery of electric field in the bioreactor chamber with no detection of current density fluctuation in the proposed model. The custom-built bioreactor with capacitive stimulation delivery system features long-term stimulation with homogeneous electric field, biocompatible, sterilisable, scalable design and cost-effective in the manufacturing process. Using a continuous stimulation regime of 100 and 200 mV/mm on cp Ti discs, viability tests revealed up to an approximately 5-fold increase of cell proliferation rate as compared to non-stimulated controls. The human mesenchymal stem cells showed more elongated and differentiated morphology under this regime, with evidence of nuclear elongation and cytoskeletal orientation perpendicular to the direction of electric field. The continuous stimulation did not cause pH fluctuations and hydrogen peroxide production caused by Faradic reactions, signifying the suitability for long-term toxic free stimulation as opposed to the commonly used direct stimulation regime. An approximate of 4-fold increase in alkaline phosphatase production and approximately 9-fold increase of calcium deposition were observed on 200 mV/mm exposed samples relative to non-stimulated controls. It is worth noting that early stem cell differentiation and matrix production were observed under the said electric field even without the presence of chemical inductive growth factors. Statement of significance: This manuscript presents a study on combining pure titanium (primarily preferred as medical implant materials) and electrical stimulation in a purpose-built bioreactor with capacitive stimulation delivery system. A continuous capacitive stimulation regime on titanium disc has resulted in enhanced stem cell orientation, nuclei elongation, proliferation and differentiation as compared to non-stimulated controls. We believe that this manuscript creates a paradigm for future studies on the evolution of healthcare treatments in the area of targeted therapy on implantable and wearable medical devices through tailored innovative electrical stimulation approach, thereby influencing therapeutic conductive and electroactive biomaterials research prospects and development. Graphical Abstract: Image, graphical abstract